Excessive reassurance seeking versus compulsive checking in OCD: Comparing implicit motivators and mechanisms. (June 2022) - Champion, Sophie M.; Grisham, Jessica R.
Abstract: Background and objectives: Excessive reassurance seeking (ERS) in OCD increases following scenarios with high threat and personal responsibility, but the mechanism via which ERS addresses these concerns is unclear. We investigated whether reassurance following OCD-related threats facilitated temporary threat re-appraisal and/or transferred responsibility to others. We also examined the 'checking by proxy' theory of OCD ERS by comparing the functional mechanisms of reassurance and checking behaviour. Methods: Community participants ( N  = 398) were recruited through MTurk and randomised to one of four conditions: ambiguous object-derived (checking) information, ambiguous person-derived (reassurance) information, unambiguous object-derived information and unambiguous person-derived information. Participants read scenarios that conveyed a risk of harm or contamination before imagining receiving reassurance or checking information as per their condition. Ratings of personal and external responsibility, threat likelihood and uncertainty were made before and after receiving the information. Results: In support of a checking by proxy hypothesis of ERS, participants in the unambiguous information conditions reported decreased uncertainty, decreased estimated threat likelihood and increased responsibility of others, regardless of whether they imagined checking or receiving reassurance. Those in the ambiguous conditions reported no changes in threat estimation or responsibility beliefs. OCD symptom level moderated responses to ambiguity: unlike low OCD, high OCD participants did not respond differentially to ambiguous versus unambiguous reassurance. Limitations: The study was performed online due to Covid-19 restrictions and utilised non-clinical participants. Conclusions: Like checking, reassurance facilitates short-term threat re-appraisal and diffuses responsibility following obsessive threats. Differentiated responses to reassurance ambiguity disappear as OC symptoms increase. Highlights: Compared the mechanisms of reassurance and checking in an online sample. Unambiguous reassurance facilitates responsibility transfer and threat re-appraisal. Ambiguous reassurance prevents responsibility transfer and threat re-appraisal. Reassurance and checking produce comparable short-term cognitive benefits. OCD symptoms moderate the impact of ambiguous versus unambiguous reassurance.